Determination of 24 pesticide residues in fortified wines by solid-phase microextraction and gas chromatography tandem mass spectrometry - Martins, Joana (2013)
The present work describes a solid-phase microextraction (SPME) gas chromatography_tandem mass spectrometry (MS/MS) method to quantify 24 pesticides in fortified white wine and fortified red wine. In this study “fortified wine” refers to a wine in which fermentation is arrested before completion by alcohol distillate addition, allowing sugar and alcoholic contents to be higher (around 80-100 g/L total sugars and 19-22% alcohol strength (v/v)). The analytical method showed good linearity, presenting correlation coefficients (R2) ≥ 0.989 for all compounds. Limits of detection (LOD) and quantitation (LOQ) in the ranges of 0.05-72.35 and 0.16-219.23 μg/L, respectively, were obtained. LOQs are below the maximum residue levels (MRL) set by European Regulation for grapes. The proposed method was applied to 17 commercial fortified wines. The analyzed pesticides were not detected in the wines tested.